The Moderating Effect Of Decision-Maker On The Relationship Between Strategy And Organizational Structure - Matseshe, Levius Koyio; Arasa, Robert; Yohannes, Tecle H (My University, 2017)
The purpose of this study was to establish the influence of the decision maker on the relationship between strategy and organization structure. The study was informed by the apparent dearth of empirical evidence about the said relationships. Whereas the relationship between strategy and structure is rich in empirical data, the role of the decision-maker in the process of structuring organizations has largely been underscored in theory that the process is neither necessarily logical nor objective. The main objective of the study was to establish the influence of the decision-maker on the relationship between strategy and organizational structure. The study was based on the cross-sectional survey targeting all manufacturing firms in Nairobi and its surrounding. Data was initially analysed by exploratory and confirmatory factor analysis tests, however, the final analysis was done using structural equation modelling. The findings established significant influence of strategy on organization structure. Further, the findings provided evidence that the decision maker has significant moderating effect on the relationship between strategy and organization structure in the manufacturing firms in Kenya. The study has thus yielded a high empirical validity for its theoretical model that was to establish; the moderating effect of the decision-maker in the relationship between strategy and organization structures. Accordingly, the assumption held within the structure-contingency model that the linkage between strategy and structure is logical and direct is no longer tenable.
Keywords: Decision-Maker; Strategy and Organizational Structure